A hospital-based case-control study of urinary bladder cancer in relation to occupational exposure to acids in the Campania Region of Italy, 1988-1990 - Soskolne, Colin L.; Jhangri, Gian S.; Pagano, Giovanni; Botte, Gerardo; Di Cintio, Patrizia; Khullar, Atul; Acid Study Group, Pascale-Cardarelli (European Journal of Oncology and Environmental Health, 2017)
Background. The lifetime risk for urinary bladder cancer in the United States ranges from 0.5%-3%, depending on gender and ethnic group, with Caucasian males having the highest rate. Occupational exposures account for one-quarter of this risk in Caucasian males, and chemicals are central to creating this workplace hazard. Past research indicates that the aryl amines, benzidine, 2-naphthalene, and aniline dyes, are the main chemicals associated with bladder carcinogenesis. Aim. Because long-term, high-level occupational exposure to strong-inorganicacid mists containing sulphuric acid is an established carcinogen, the relationship between occupational acid exposure and bladder cancer was tested as part of an extensive occupational cancer case-control study of 513 male hospitalized patients in the Campania Region of Italy. Patients and methods. The full dataset included exposure information on up to 20 major groups of occupational chemicals with the target cancers of lung (n = 111), laryngeal (n = 35), naso/nasal/pharyngeal (n = 22), oral cavity (n = 23) and bladder (n = 75). For this study, cases (n = 75) were defined as people with bladder cancer, while controls (n = 270) were other unmatched patients with oral cavity cancers (but none of the other three target cancers) or patients with any other reason for hospitalization. Unconditional logistic regression was used to fit the acid-bladder cancer model controlling the effects of tobacco and age. Other confounders, such as alcohol and coffee consumption (the only dietary variable in our dataset) are discussed and considered, but neither was significant. Results. The results demonstrate an adjusted statistically significant association between occupational acid exposure and bladder cancer (OR = 4.09; p = 0.028). Discussion. The implications of this new finding in humans are discussed, both in the context of existing evidence, and in light of the 1992-IARC designation based on research to that time demonstrating the rôle of acid mixtures in the causation of upper respiratory tract cancers. Conclusion. Further research is warranted to replicate this finding.